Bingkai Identitas dalam Konflik Geopolitik: Intervensi Militer Rusia di Ukraina - Rizky Widiasa (Intermestic: Journal of International Studies, 2018)
This article is written to analyze the conflict between Russia and Ukraine that led to the fall of Krimea. Russia defends its act by stating that the annexation of Krimea was an effort to protect Russian ethnicities from the political turmoil happened during revolutionary movement. By specifically analyzing the similarities on identity between Ukraines in Crimea with Russian ethnicities, this article argues that bounded historical similarities could trigger states to oppress other to achieve its geopolitical ambition. This article revealed that certain similar identities by some states could be used as an instrument to justify a unilateral action towards other country.